UJI OPTIMASI ADSORBEN ALOFAN DAN PASIR KUARSA PADA ADSORPSI LOGAM BESI (Fe) - Nuzulul Anggi Rizki; Lies Wuryanita Adriyani; Khairunisa (Nusantara Hasana Journal, 2025)
The increasingly rapid development of industry can cause environmental pollution from the wastewater produced. Industrial wastewater contains heavy metal ions, one of which is iron (Fe). The danger of Fe metal can have a negative impact on living things and the environment so it needs to be minimized and eliminated. Adsorption has been proven to be an effective method in reducing the levels of heavy metal ions in waste. In the adsorption process, the most important thing is the adsorbent. Allophane and quartz sand are natural materials that can be used as adsorbents. This study is expected to determine the adsorbent capacity of allophane and quartz sand against iron (Fe) metal ions. The adsorption process was carried out in 2 variations, namely variations in the mass composition of the adsorbent (0:100; 25:75; 50:50; 75:25; 100:0) and variations in contact time (15, 30, 60, 90, 120). Measurement of adsorption capacity using Atomic Absorption Spectroscopy (AAS). The results showed that the optimal results for variations in the mass composition of allophane and quartz sand adsorbents were 50:50 with an adsorption capacity of 0.81325 mg/g and an absorption percentage of 67.67%. The optimal contact time was 60 minutes with an adsorption capacity of 0.81677 mg/g and an absorption percentage of 67.97%. This study showed that a mixture of allophane and quartz sand can be used as an effective adsorbent for the adsorption of heavy metal iron (Fe).